(untitled) (Scientific journal of the Fergana State University, 2025)
The following article investigates the effectiveness of the newly established “Flipped classroom” method into EFL classes in teaching phrasal verbs. As of the most difficult language components, phrasal verbs require a special attention in the teaching process. The findings can illustrate the successful alliance of the flipped method and phrasal verbs retaining an engaged and intriguing learning atmosphere in the classroom.